Effect of repeated Superovulation on superovulatory response and embryo recovery in Sahiwal cows - MISHRA, U K; MISHRA, O P; KHAN, J R (The Indian Journal of Animal Reproduction, 2023)
Twelve elite Sahiwal donor cows were repeatedly superovulated four to five times with an interval of 75 to 100 daysbetweentwosuperovulations to . determine the effect of respeated gonadotrophicsuperstimulation of ovaries on superovulatory response and embryo recovery during a period of one year. The mean numbers of corpus luteum / ovulations observed were 10.16±0.62, 9.75±0.64,7.75±0.56, 5.91±0.37 and 4.66±0.87 in five attempts respectively. The mean number of embryo recovery was 6.83±0.70, 4.83±0.52, 3.41±0.35, 3.08±0.39 and 2.33±0.87. The mean number of transferable embryo was 5. 16±0.65, 3.5±0.37, 2.5±0.31, 2.0±0.27 and 2.0±0.57. Repeated superstimulation of ovaries by exogenous gonadotropin treatments had a tendency towards decreasing number of ovulations,. embryo recovery and transferable embryos per cow during a period of one year. It is also observed that in one year fiverepeatedsuperovulations and flushing were possible only in 25% Sahiwal donors whereas in 75% cows only four repeated superovulation and embryo recovery were done successfully.
Keywords: Superovulation; embryo recovery; Sahiwal cows